LA ERMITA DE LA SOLEDAD DE CEHEGÍN (MURCIA): HISTORIA Y ARTE PROMOVIDO POR UNA COFRADÍA - de la Ossa Giménez, Elena (Imafronte, 1995)
The hermitage of Nuestra Señora de la Soledad in Cehegín (Murcia) housed the brotherhood of the same name following its foundation in 1595, by Apostolic Bull, with the title of Hospitality and Brotherhood. The original 16th century building must have been a single-nave church, which remained practically unchanged until the second decade of the 17th century, when it was completely transformed into three aisles and four sections. The impressive tower, dating from 1788, is a mixture of traditional Baroque and neoclassicism, which has come to be known as classical Baroque. The most interesting aspect is undoubtedly the fine collection of altarpieces and sculptures from the 16th, 17th and 18th centuries, particularly those of San Nicolás, Resucitado, Santo Cristo, Virgen de la Soledad, San Francisco Javier and San Juan Evangelista.